Tantangan Belajar-Mengajar Kalkulus: Studi Naratif pada Gaya Kognitif dan Self-Confidence Calon Guru - Agus Suyanto (Pendidikan Matematika STKIP Kusuma Negara, 2021)
In the 21st century, it was introduced with sains, technology, engineering mathematics (STEM). Routine aspects of current teaching practice have little time to discuss the basic concepts of calculus, while teacher competence in learning has a long-term effect on students. The purpose of this study was to determine how the challenges of teaching and learning calculus prospective teachers based on cognitive style and self-confidence. This research uses a qualitative approach, a narrative perspective, and a descriptive design. The research sample was selected purposively from seven prospective teachers in a university. Data were collected using the group embedded figures test (GEFT) for the category of cognitive style types, self-confidence questionnaires, and interviews regarding teaching and learning challenges. The result of the research is that the challenge of teaching and learning is a factor that arises due to mastery of mathematical content, pedagogical competence, experiencing anxiety, and learning experiences in mathematics class.